THE ROLE OF A SPORT IN A HEALTHY LIFESTYLE - Asatullayev Rustam Bakhtiyorovich; Sirojboyev Shahzod Vohidovich (TADQIQOTLAR, 2026)
Abstract: This article explores the significant role of sports in promoting a healthy lifestyle. It discusses how regular participation in sports contributes to physical fitness, mental well-being, and social interaction. The article highlights the various health benefits associated with engaging in sports, including improved cardiovascular health, enhanced muscle strength, and better flexibility. Additionally, it emphasizes the positive impact of sports on mental health, such as reduced stress and anxiety levels, improved mood, and increased self-esteem. The social aspect of sports is also examined, illustrating how team participation fosters community, teamwork, and communication skills. Overall, the article advocates for the incorporation of sports into daily routines as a vital component of holistic health.